Dakwah Digital Cara Kreatif Menyebarkan Nilai Islam di Media Sosial Tiktok untuk Generasi-Z - Dhaefan Fahrudy; Evril Rizkya Haryani; Nazwa Nur Aulia Rahman; Muhamad Parhan (Ad-DA'WAH, 2026)
Abstract This study examines digital da'wah on TikTok as a creative medium for spreading Islamic values to Generation Z. As digital natives, they prefer short, visual, and interactive content, making TikTok a strategic platform for religious communication. The research applies a descriptive qualitative method with Qualitative Content Analysis. Primary data were obtained through non-participant observation of four popular Islamic TikTok accounts (February–August 2025), while secondary data were drawn from relevant literature. Findings show that strategies such as personal storytelling, short educational videos with visual text, aesthetic Islamic motivation, and light humor effectively engage Generation Z. The Islamic values conveyed include aqidah, akhlaq, fiqh ibadah, and spirituality, presented in concise and adaptive formats. Audience engagement appears through comments, likes, shares, and participation via duet and stitch features.The study concludes that the effectiveness of digital da'wah depends on the preacher’s creativity in packaging brief, relevant, and appealing messages. TikTok thus serves not only as a medium of religious education but also as a tool for moral and spiritual development among youth in the digital era.